The proteogenomic subtypes of acute myeloid leukemia - Jayavelu, Ashok Kumar; Wolf, Sebastian; Buettner, Florian; Alexe, Gabriela; Häupl, Björn; Comoglio, Federico; Schneider, Constanze; Döbele, Carmen; Fuhrmann, Dominik Christian; Wagner, Sebastian; Donato, Elisa; Andresen, Carolin; et al. (Cancer cell, 2022)
Acute myeloid leukemia (AML) is an aggressive blood cancer with a poor prognosis. We report a comprehensive proteogenomic analysis of bone marrow biopsies from 252 uniformly treated AML patients to elucidate the molecular pathophysiology of AML in order to inform future diagnostic and therapeutic approaches. In addition to in-depth quantitative proteomics, our analysis includes cytogenetic profiling and DNA/RNA sequencing. We identify five proteomic AML subtypes, each reflecting specific biological features spanning genomic boundaries. Two of these proteomic subtypes correlate with patient outcome, but none is exclusively associated with specific genomic aberrations. Remarkably, one subtype (Mito-AML), which is captured only in the proteome, is characterized by high expression of mitochondrial proteins and confers poor outcome, with reduced remission rate and shorter overall survival on treatment with intensive induction chemotherapy. Functional analyses reveal that Mito-AML is metabolically wired toward stronger complex I-dependent respiration and is more responsive to treatment with the BCL2 inhibitor venetoclax.
Online veröffentlicht am 3. März 2022, Artikelversion 14. März 2022
Gesehen am 31.01.2023